Research on the performance of digital signal processing in financial market predictions - Li, Pian (Nanyang Technological University, 2020)
This report presents the research method and result of the project titled Research on the Performance of Digital Signal Processing in Financial Market Predictions. In this report, three Digital Signal Processing (DSP) methods: Fast Fourier Transform, Linear Predictive Coding and Wavelets Transform are introduced and discussed. The prediction performance is aggerated and displayed in a responsive web application. Through this report, readers will have a comprehensive understanding of the performance of DSP application in financial market prediction. This report also guides readers with the instruction of the web application to provide an investment reference in real life.